The salt- tolerance of some Phosphate-solubilizing bacteria strains - Ha, Pham Thanh; Quynh Mai, Nguyen Thi; Phuong Chi, Nguyen Thi (Academia Journal of Biology, 2015)
The reproduction and the phosphate-solubilizing ability of ten bacterial strains in different NaCl concentrations (0 %, 1%, 2%, 3%, 4%, 5%) have been studied. The experiments carried out under shaking condition (180 rpm.) for 48 h  at 30oC. Based on the cell densities of cultured broth, we divided 10 strains into 4 groups. The group 1 (well reproductive in the 0% and 1% NaCl mediums) consisted of two strains RTL7, DTL2.2. The group 2 (well reproductive in the 0%, 1%, 2% NaCl mediums) consisted of three strains: RLT6, Q5.2, DDP5. The group 3 (well reproductive in the 0%, 1%, 2%, 3% NaCl mediums) consisted of three strains RTL1, RTL3, DTL4. The group 4 was well reproductive in all 6 different NaCl concentrations. All ten bacterial strains showed the phosphate- solubilizing ability after 48 hours incubating. Five strains had the highest phosphate-solubilizing ability in the presence of 2% salt (NaCl). They were DTL2.2, RTL6, Q5.2, RTL1 and IIIe strains. Five rest strains solubilized most tricalcium phosphate in the presence of 3% NaCl.